Effect of Tamsulosin in Prevention of Postoperative Urinary Retention: Effect of Tamsulosin on Postoperative Urinary Retention - Buriro, Faheem; Altaf, Javed; Ishaque, .; Ali, Imdad; Ali, Majid; Ali, Mansoor (Pakistan Journal of Health Sciences, 2026)
Tamsulosin has shown effectiveness in the treatment of lower urinary tract symptoms, especially post-operative urinary retention (POUR). Objectives: To assess the efficacy of tamsulosin in the prevention of POUR and to determine the relationship between POUR incidence and urinary parameters such as urine pH, specific gravity, and color. Methods: This cohort (longitudinal) research was carried out at the Department of Urology, Liaquat University of Health Sciences, Jamshoro, for 6 months (from January 2025 to June 2025) after approval from the IRB. Data collection included baseline demographics, comorbidities, and pre-operative information. At 6, 12, and 24 hours post-operative post-void residual (PVR) was assessed. Analysis of urine was done for measuring urinary pH, color, and specific gravity. SPSS was used for analyzing the data, keeping p<0.05 statistically significant. Results: From 150 post-operative cases, the mean age was 53.5 ± 11.3 years, with around 71 % male. Tamsolusin substantially decreased POUR with a reduction in PVR from 186 ml (6 hours) to 82 ml (24 hours). Incidence of POUR reduced from 24.7 % to 6 %. Cases having POUR showed lower pH of urine, high specific gravity, and dark colored urine. Conclusions: The present study demonstrated that tamsulosin was effective in preventing postoperative urinary retention (POUR) by significantly reducing post-void residual volumes and improving urinary flow within the first 24 hours after surgery.